2019
DOI: 10.2147/ott.s227217
|View full text |Cite
|
Sign up to set email alerts
|

<p>A Gallbladder Carcinoma Patient With Pseudo-Progressive Remission After Hydrogen Inhalation</p>

Abstract: BackgroundHydrogen therapy has been reported to convert exhausted programmed cell death receptor (PD-1)+CD8+ T cells to PD-1-CD8+ T cells, in advanced colorectal cancer patients, which is associated with significantly prolonged survival.Case presentationA 72-year-old female patient presented with metastatic gallbladder cancer and underwent symptomatic treatment combined with hydrogen therapy. The tumors were initially enlarged and displayed increased tumor marker expression following hydrogen inhalation therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…After one month of hydrogen inhalation, the patient showed obvious pseudo-progression of the disease and quickly relieved after symptomatic treatments. 6 After 2 months of hydrogen inhalation, the patient's performance status showed significant improvement (decreased from 5 to 3). After 3 months of hydrogen inhalation, tumor markers were reduced to the normal reference range, and CT showed more than a 50% reduction in gallbladder tumors and multiple intrahepatic and hilar metastases (defined as partial response).…”
Section: R Eal W Orld E Vidence Of H Ydrogen O Ncolmentioning
confidence: 94%
“…After one month of hydrogen inhalation, the patient showed obvious pseudo-progression of the disease and quickly relieved after symptomatic treatments. 6 After 2 months of hydrogen inhalation, the patient's performance status showed significant improvement (decreased from 5 to 3). After 3 months of hydrogen inhalation, tumor markers were reduced to the normal reference range, and CT showed more than a 50% reduction in gallbladder tumors and multiple intrahepatic and hilar metastases (defined as partial response).…”
Section: R Eal W Orld E Vidence Of H Ydrogen O Ncolmentioning
confidence: 94%
“…Up until now, more than 800 original papers regarding the medical use of H 2 , including approximately 70 clinical trials, have been reported. As observed from the production of H 2 in the intestines, adverse effects caused by H 2 has not been observed in many clinical studies [ 40 , 41 , 42 , 43 , 44 , 45 , 46 ]. In recent papers, we reviewed that H 2 is promising for medical applications due to its marked efficacy and for having no adverse effects [ 47 ].…”
Section: H 2 As a Mitochondria-targeted ·Oh Scamentioning
confidence: 99%
“…We believe that the inhalation of H 2 is suitable for use as a radioprotective agent. In addition, H 2 has no safety issues, because no side effects have been observed in clinical trials [ 10 , 64 , 66 , 69 , 72 , 73 , 74 , 75 , 76 , 77 ] and from the fact that H 2 does not affect normal tissues and cells [ 78 ].…”
Section: Prospects Of H 2 As a Radioprotective Agentmentioning
confidence: 99%